Global hip-hop culture and the scopophilic spectacle of women in South African hip-hop music videos - Ntebaleng Mpetsi; Toks Oyedemi (Communicare)
In many hip-hop music videos, women’s value is reduced to sensuous display of sexuality. As a result visual pleasure is created through the representation of women as eager and willing sexual objects. This article assesses the techniques and ways women are sexualised in South African hip-hop music videos, and how their representation attempts to create visual pleasure for those that consume these videos. Four critical elements are adopted from Laura Mulvey’s seminal theoretical discourse about the positioning of women in narrative cinema, to study the gender representation and sexual presentation of women in two popular South African hip-hop music videos. The analysis reveals that appealing to the male gaze, processes of objectification, gender division of labour and camera techniques are ways of presenting a sexualised spectacle of women for the visual pleasure of male characters and audiences of the videos.